Pengaruh Implementasi Garret's Element Terhadap Aksesibilitas Website Rumah Sakit Bagi Disabilitas Netra - Andi Jamiati Paramita; Mirandha Ariesca; Muh. Ihsan Ramadhan (Program Studi Teknik Komputer, 2023)
Hospital website accessibility is still a problem that is often faced by users with disabilities, especially the blind who have special needs related to vision (visual). The main obstacle for users with visual disabilities is the complex information architecture so that the use of the features available on the hospital's website has not been fully enjoyed. Likewise, the information presented by the hospital website interface cannot be conveyed to users with visual disabilities. This is because there are still many interface designs (UI/UX) for hospital websites that are not based on the needs of users with disabilities. This study aims to see the effect of implementing Garret's Element on hospital websites for users with visual disabilities by applying Garret's UX Element method to design hospital website interfaces through 5 stages, namely Strategy Plane, Scope Plane, Structure Plane, Skeleton Plane and Surface Plane. Measurements were taken by observation and the results obtained were that users stated that designing the UIUX of a hospital website by applying Garret's UX Elements required less time to obtain information than websites that did not apply this method.